2019
DOI: 10.1101/622571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromesodermal progenitors separate the axial stem zones while producing few single- and dual-fated descendants

Abstract: Most embryos and regenerating tissues grow by the action of stem zones. Two epithelial stem zones drive axial elongation in amniotes: the mature organizer generates mesoderm, the neuralised ectoderm around it extends the neuraxis. Bipotential progenitors were also shown to exist. How are these stem cell populations organised and what controls the cell fate of bipotential progenitors? We use direct, in vivo imaging of these stem cells in the chick. We find that progenitors of single and dual fates are mingled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Alternatively, cell movements within the region may determine the proportion of cells that end-up into either neural or mesodermal progenitor compartments where cells receive alternate signal exposure and only then become specified (i.e., cell fate is “conditioned” by the signals a cell receives as it is displaced into either progenitor compartment). The latter model has been supported by recent work in chick embryos, where large scale cell movements in the region have been observed to correlate with NM cell fate ( Wood et al, 2019 ). In this review, we will outline how NM differentiation is a good experimental system in which to disentangle this complex relationship between the dynamic cell behaviors driving tissue morphogenesis and cell fate specification, and to investigate how this can generate robustness to developmental systems.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Alternatively, cell movements within the region may determine the proportion of cells that end-up into either neural or mesodermal progenitor compartments where cells receive alternate signal exposure and only then become specified (i.e., cell fate is “conditioned” by the signals a cell receives as it is displaced into either progenitor compartment). The latter model has been supported by recent work in chick embryos, where large scale cell movements in the region have been observed to correlate with NM cell fate ( Wood et al, 2019 ). In this review, we will outline how NM differentiation is a good experimental system in which to disentangle this complex relationship between the dynamic cell behaviors driving tissue morphogenesis and cell fate specification, and to investigate how this can generate robustness to developmental systems.…”
Section: Introductionmentioning
confidence: 66%
“…By maintaining a population of uncommitted progenitor cells at the posterior aspect of the embryo, multiple aspects of their developmental dynamics can be altered to compensate for proportional changes in tissue sizes more anteriorly. This could be achieved by altering the proportional expansion of the progenitor population itself, as seen by differences in the clonal dynamics of NM populations between zebrafish, mouse and chicken embryos ( Tzouanacou et al, 2009 ; Attardi et al, 2018 ; Wood et al, 2019 ; Guillot et al, 2020 ). Alternatively, it could be by altering the balance between N and M fates derived from the region and the metabolic mechanisms described above might impact this process directly ( Bulusu et al, 2017 ; Oginuma et al, 2017 , 2020 ).…”
Section: Maternal-embryo Trade-offs In Evolution and How This Impactmentioning
confidence: 99%
“…The observation that many T −/− NMPs become trapped in the primitive streak, rather than produce excess neural tissue, suggests that at the single-cell level in the intact embryo, many NMPs may not have both somitic and neural differentiation options available to them, possibly due to spatial constraints. Indeed, although in vivo lineage tracing suggest widespread bipotency for larger NMP clones ( Tzouanacou et al., 2009 ), heterotopic transplantation and live-cell imaging studies suggest that many cells with NMP potential will only differentiate into one lineage in the embryo ( Wood et al., 2019 ; Wymeersch et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these studies revealed the existence of single progenitors able to give rise to only neural or mesodermal cells but also pointed out to the existence of a third type of progenitor able to generate both neural and mesodermal cells. These bi-potential progenitors, named neuro-mesodermal progenitors (NMPs), have later been shown to exist in zebrafish (10) and in bird embryos (48,50,51). In the early bird embryo (stage HH4-7), the future posterior progenitors are initially located in anterior epithelial structures: the epiblast and the primitive streak.…”
Section: Introductionmentioning
confidence: 99%